105 A third-generation human GUCY2C-targeted CAR-T cell for colorectal cancer immunotherapy. (10th December 2020) - Baybutt, Trevor; Snook, Adam; Waldman, Scott; Stem, Jonathan; Caparosa, Ellen; Zalewski, Alicja
Abstract : Background: Colorectal cancer (CRC) presents a significant public health burden, responsible for the second most cancer-related deaths in the United States, with an increasing incidence in young adults observed globally. 1, 2 While the blockade of immune checkpoints received FDA approval as a CRC therapeutic, only patients with microsatellite instability, accounting for 15% of sporadic cases, demonstrate partial or complete responses. 3 We present a third-generation chimeric antigen receptor (CAR)-T cell directed towards the extracellular domain of the mucosal antigen guanylyl cyclase C (GUCY2C), which is over-expressed in 80% of CRC cases, as a therapeutic alternative for late stage disease. Here, we demonstrate that human GUCY2C CAR-T cells can selectively kill GUCY2C-expressing colorectal cancer cells in vitro and produce inflammatory cytokines in response to antigenic stimulation. Methods: Peripheral blood mononuclear (PBMCs) cells were isolated from leukoreduction filters obtained from the Thomas Jefferson University Hospital Blood Donor Center (IRB #18D.495). Magnetic Activated Cell Sorting (MACS) technology was used to negatively select pan-T cells (Miltenyi Biotec), followed by activation and expansion using anti-CD3, anti-CD28, and anti-CD2 coated microbeads (Miltenyi Biotec) and supplemented with IL-7 and IL-15 (Biological Resources Branch Preclinical Biologics Repository – NCI). T-cells were transduced with a lentiviral vector encoding the anti-GUCY2C CAR. Our CAR utilizes a single chain variable fragment of human origin directed towards the extracellular domain of GUCY2C, the CD28 hinge, transmembrane, and intracellular signaling domain (ICD), 4-1BB (CD137) ICD, and CD3ζ ICD. CAR-T cells were used for experiments between 10 to 14 days after activation in vitro using the xCELLigence real time cytotoxicity assay and intracellular cytokine staining. Results: GUCY2C-directed CAR-T cells specifically lysed the GUCY2C-expressing metastatic CRC cell line T84, while the control CAR did not. GUCY2C-negative CRC cells were not killed by either. In addition to cell killing, GUCY2C-directed CAR-T cells of both the CD8 + and CD4 + co-receptor lineage produced the inflammatory cytokines IFN-γ and TNFα in response to GUCY2C antigen. Conclusions: We demonstrate that human GUCY2C-directed CAR-T cells can selectively target GUCY2C-expressing cancer cells. We hypothesize that GUCY2C-directed CAR-T cells present a viable therapeutic option for metastatic CRC. In vivo animal models to examine this potential are currently on-going. Acknowledgements: This work was supported by the Department of Defense Congressionally Directed Medical Research Programs (W81XWH-17-1-0299, W81XWH-191-0263, and W81XWH-19-1-0067) to AES and Targeted Diagnostic & Therapeutics to SAW. AES is also supported by a DeGregorio Family Foundation Award. SAW is supported by the National Institutes of Health (NIH) (R01 CA204881, R01 CA206026, and P30 CA56036), and the Department of Defense Congressionally Directed Medical Research Program W81XWH-17-PRCRP-TTSA. SAW and AES were also supported by a grant from The Courtney Ann Diacont Memorial Foundation. SAW is the Samuel M.V. Hamilton Professor of Thomas Jefferson University. JS, EC, and AZ were supported by an NIH institutional award T32 GM008562 for Postdoctoral Training in Clinical Pharmacology. Ethics Approval: This study was approved by the Thomas Jefferson University Institutional Review Board (IRB Control #18D.495) and the Institutional Animal Care and Use Committee (Protocol #01529). References: Siegel RL, Miller KD, Jemal A. Cancer statistics, 2020. CA Cancer J Clin 2020;70: 7–30. doi:10.3322/caac.21590 Araghi M, Soerjomataram I, Bardot A, Ferlay J, Cabasag CJ, Morrison DS, et al. Changes in colorectal cancer incidence in seven high-income countries: a population-based study. Lancet Gastroenterol Hepatol 2019;4: 511–518. doi:10.1016/S2468-1253(19)30147-5 Overman MJ, McDermott R, Leach JL, Lonardi S, Lenz H-J, Morse MA, et al. Nivolumab in patients with metastatic DNA mismatch repair-deficient or microsatellite instability-high colorectal cancer (CheckMate 142): an open-label, multicentre, phase 2 study. Lancet Oncol 2017;18: 1182–1191. doi:10.1016/S1470-2045(17)30422-9